Penguatan Profil Pelajar Pancasila Menggunakan Model Value Clarification Technique (VCT) Tipe Percontohan Pada Pendidikan Pancasila Sekolah Dasar - Soma Triharyoso; Maha Lastasa Buju Basafpipana Habaridota; Syarifah Asmiati (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study describes the strengthening of the Pancasila Student Profile using the Value Clarification Technique (VCT) model in the Civics Education learning of the topic